Evolution of tectono-sedimentary systems in the Kumano Basin, Nankai Trough forearc. (November 2015) - Moore, G.F.; Boston, B.B.; Strasser, M.; Underwood, M.B.; Ratliff, R.A.
Abstract: Sedimentary deposits in the distal Kumano forearc basin of the Nankai accretionary margin off Kii Peninsula, Japan, have been imaged using three-dimensional (3D) seismic data. The seismic data, along with logging and core data from the Integrated Ocean Drilling Program (IODP) show that the unconformity between the accretionary prism and overlying forearc sediments is time-transgressive. The unconformity at Site C0002 separates 5 Ma prism rocks from 3.65 Ma basin deposits; at Site C0009 it separates 5.6 Ma prism from 3.8 Ma basin sediments. Acoustic reflections in the basal deposits are sub-parallel to the underlying accretionary prism; the acoustic facies varies in thickness from 50 to 750 m. The mudstone deposits and laterally equivalent turbidites are interpreted as lower trench-slope deposits. The condensed slope sediment (SS) section decreases in age from 3.5 to 1.5 Ma at Site C0002 to 1.5–0.9 Ma at C0009. Acoustic sequences within the lower forearc basin (LFB) contain higher proportions of silt and sand turbidites and progressively onlap the SS unit along a low-angle discontinuity (KL) in a landward direction. Because of the landward onlap of the LFB unit, the oldest LFB strata at C0002 are older than 1.67 Ma, whereas those at C0009 are younger than ∼0.9 Ma. Thus, the amount of time missing or characterized by condensed sedimentation across the KL unconformity decreases in duration in the landward direction. The landward-onlapping sequences tilt progressively landward in response to regional uplift along an out-of-sequence thrust (OOST; mega-splay) fault. Regional tilting shifted the basin's depocenter progressively landward, expanding that part of the basin from ∼10 km in width to >30 km. The onset of sand-silt turbidite deposition in the distal basin began after more accommodation space was created by the uplift of the outer ridge along the splay fault at ∼1.9 Ma. Conversely, turbidites of the Upper Forearc Basin (UFB) progressively onlap LFB in a seaward direction. Furthermore, the respective thicknesses of the LFB and UFB units switch from the seaward side of the basin (C0002) farther landward (C0009): the LFB unit is > 800 m thick in the seaward region, whereas it is only 200–300 m thick in the landward region; the UFB unit is < 50 m thick in the seaward region, and up to 600 m thick in the landward region. Thus, Kumano Basin responded in both space and time to a complex interplay between tectonics and sedimentation. The stratigraphy records a balance between the effects of prism uplift along the basin's distal edge with the rerouting of channels and canyons along the basin's proximal edge. Highlights: Kumano Basin evolution controlled by frontal accretion and out-of-sequence faulting. Uplift along megasplay fault at 2.0 Ma created forearc basin accommodation space. Diachronous facies boundary separates slope sediments from basin strata.